The Hacker Crackdown: Law and Disorder on the Electronic Frontier - Sterling, Bruce, 1954- (Salt Lake City, UT : Project Gutenberg, 1994)
"The Hacker Crackdown: Law and Disorder on the Electronic Frontier" by Bruce Sterling is a historical account written in the early 1990s. The book explores the burgeoning world of cyberspace and the complex interplay between hackers, law enforcement, and telecommunications companies, particularly highlighting the significant Hacker Crackdown of 1990, during which government agents targeted the electronic underground and its players. The opening portion of the work sets the stage for a discussion on the changing nature of communication technologies and the legal landscape surrounding them, beginning with a significant incident on January 15, 1990, when a massive telephone system failure at AT&T caused widespread disruption. Bruce Sterling outlines the perceptions and fears of law enforcement regarding hackers, revealing a sense of paranoia following the crash, which some suspected was due to malevolent hacking. This part introduces the complicated dynamics between different stakeholders in cyberspace, such as police, telephone companies, and the hacker community, serving as a prelude to a deeper investigation into the events that shaped the digital environment of that era. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Hacker_Crackdown
Release date is 1994-01-01
Keywords: Computer crimes -- United States; Telephone -- Corrupt practices -- United States; Computer programming -- Corrupt practices -- United States